DETERMINASI STRUKTUR MODAL EMPIRIS PADA PERUSAHAAN YANG TERDAFTAR DI BURSA EFEK INDONESIA DI SEKTOR MAKANAN PERIODE 2021-2022 - Aulia Rahma; Imron Rosyadi (POLITEKNIK LP3I JAKARTA, 2025)
The aim of this research is to study how capital structure, business size and profitability impact stock returns in companies in the food sector listed on the Indonesia Stock Exchange (BEI) during the 2021-2022 period. The research method uses a quantitative approach with data analysis techniques using SmartPLS. The research results show that capital structure has a large impact on stock returns, with a strong positive relationship. Company size also has a positive and significant effect on stock returns, which shows that businesses have a large scale which tends to produce higher stock returns. Profitability was found to play an important role in increasing company value, but not as an intervening variable in the relationship between capital structure and company size on stock returns. This research shows the importance of effective capital structure management and targeted growth strategies to improve stock performance and company investment attractiveness. The limitation of this research is that it focuses on the food sector and includes limited variables, so further research is recommended to expand the analysis of sectors and variables.